Kesalahan Penulisan Arab Melayu Dalam Teks Bacaan Pisang Berbuah - Hasnah Faizah AR; Dwi Mulyani; Nike Tri Juliana (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Malay Arabic writing is writing that uses Arabic script or letters (hijaiyah) in the Malay language. Malay Arabic script is often developed as a series of reading texts. Reading Malay Arabic texts is a means of learning Malay culture, but incorrect spelling can cause misunderstandings for readers. This research will examine Malay Arabic writing errors found in the fruitful banana advice text. The type of research used in this study is qualitative. The results of this study were that spelling errors were found, letters were missing when writing words, and discrepancies in meaning when written in Arabic-Malay letters.